ASPECT OF THE NIKE CAJUN AB 6.197 FIRED 27 OCTOBER 1964 FROM FORT CHURCHILL MANITOBA, CANADA. - MARCOU,Rene J.; Sandock,John A.; Sullivan,Brian F. (1965)
The attitude of a rocket with respect to a geocentric coordinate system and a Fort Churchill coordinate system was determined. The analysis and reduction was based on data obtained from magnetometers and solar eyes mounted on the vehicle. The telemetered data consisted of magnetic field measurements from the spin and axial magnetometers and coded solar angle measurements from mutually perpendicular solar aspect eyes. (Author)